Brothers in hope : the story of the lost boys of Sudan - Williams, Mary, 1967-; Christie, Gregory, 1971- (New York : Lee & Low, 2005)
Eight-year-old Garang, orphaned by a civil war in Sudan, finds the inner strength to help lead other boys as they trek hundreds of miles seeking safety in Ethiopia, and then Kenya, before being offered sanctuary in the United States many years later.
4.3
3-6
Coretta Scott King Award, 2006
Keywords: Refugees -- Sudan -- Juvenile fiction; Self-actualization (Psychology) -- Juvenile fiction; Orphans -- Sudan -- Juvenile fiction; War -- Juvenile fiction; Sudan -- Juvenile fiction; Refugees -- Fiction; Self-actualization (Psychology) -- Fiction; Orphans -- Fiction; War -- Fiction; Sudan -- Fiction; Refugees -- Fiction; Motivation (Psychology) -- Fiction; Orphans -- Fiction; War stories; Sudan -- Fiction